The Existence of Saluang Darek in Lubuak Tarok Kenagarian, Sijunjung Regency - Radendri, Digayu; Marzam (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
This study aims to analyze the presence of saluang darek in Lubuk Tarok district, Sijunjung regency. This type of research is qualitative research with descriptive methods. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and mobile phones. The data in this study used primary data and secondary data. Data collection techniques are carried out by means of literature studies, observations, interviews and documentation. The steps of analyzing data are data collection, data reduction, data presentation and conclusion drawing. The results showed that the existence of Saluang Darek in Lubuk Tarok kenagarian experienced stages of development starting from the first entry into Lubuk Tarok, but over time people's love began to fade for this art, even in recent years the traditional art of saluang darek began to be rarely seen used by the people of Lubuk Tarok in their party events. Saluang Darek traditional art is used by the people of Lubuk Tarok in several regional art events in Lubuk Tarok, such as the traditional malam bajago bakawua adat, acara malam bajago alek nikah kawin, malam bajago tagak galai, maarak marapulai dan malam bajago Lubuk Ban fish harvest, its function is as entertainment for the people of Lubuk Tarok.